A Cross-Country Analysis of Public Debt Management Strategies - Melecky, Martin (World Bank, Washington, DC, 2012)
This paper analyzes results of a survey on debt management strategies conducted by the Banking and Debt Management Department of the World Bank. The analysis focuses on (1) whether a public debt management strategy exists in a given country, (2) whether it is made public, and (3) in which form it is imparted. The paper analyzes the distribution of the latter characteristics over different regions, income groups, and levels of indebtedness using graphical analysis. Using regression analysis, it investigates the extent to which basic economic factors can explain the characteristics of public debt management strategies across countries.